Pain catastrophizing may moderate the association between pain and secondary hyperalgesia. Issue 1 (March 2017) - Pressman, Alexander J.; Peterlin, B. Lee; Tompkins, David Andrew; Salas, Rachel E.; Buenaver, Luis F.; Haythornthwaite, Jennifer A.; Campbell, Claudia M.
Abstract : Catastrophizing, a persistent negative mental set characterized by helplessness, rumination, and magnification of pain sensations, has a potent effect on pain report and clinical outcomes. Previous studies have documented an association between cognitive factors and central sensitization. The current analysis sought to test the potential modulating effect of pain catastrophizing on the association between capsaicin pain and the region of secondary hyperalgesia. Thirty‐eight healthy individuals (50% women, mean age = 25.7, SD = 5.3) completed the Pain Catastrophizing Scale (PCS), then underwent topical application of 10% capsaicin, which was covered by a thermode maintained at 40°C for 90‐min. Following removal of the capsaicin, the region of secondary hyperalgesia was determined. Hayes' PROCESS macro was employed to examine catastrophizing's potential moderating effect, which did not reveal a significant association between capsaicin pain ratings and the region of secondary hyperalgesia (β = 15.1, p = .06). Though PCS was not associated with area of secondary hyperalgesia (β = 23.9, p = .29), a significant interaction was present between PCS and capsaicin pain ratings (β = 3.7, p = .0004). Specifically, those endorsing higher catastrophizing levels and higher pain ratings experienced the greatest areas of secondary hyperalgesia. The Johnson‐Neyman technique was used to determine the regional effect of the moderation, which indicated that when PCS scores were ≥10.6, capsaicin pain significantly moderated the association between pain and area of secondary hyperalgesia. These results suggest that catastrophizing plays an important role in the area of secondary hyperalgesia, and potentially central sensitization, warranting further testing in future research.